2021
DOI: 10.1097/rlu.0000000000003657
|View full text |Cite
|
Sign up to set email alerts
|

False-Positive Axillary Lymph Nodes on FDG PET/CT Resulting From COVID-19 Immunization

Abstract: World-wide mass COVID-19 vaccination has been deployed starting with those most vulnerable, including the elderly and cancer patients. A 70-year-old man with right lung cancer underwent staging FDG PET/CT, which demonstrated an avid right lung mass with avid hilar and mediastinal nodes. Avid left axillary nodes of benign configuration were also noted. The patient had the Oxford-AstraZeneca COVID-19 vaccination in the left arm a week earlier. On reflection, the axillary nodes were concluded to be reactive relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 9 publications
2
22
0
Order By: Relevance
“…Incidentally, the rate of apparently positive lymphnodes was signi cant in this setting. Although our ndings may appear not astonishing, they deserve caution, particularly for cancer patients as recently reported by some other authors [23][24][25]. The correct interpretation of this secondary effect of vaccine is of primary importance to avoid unnecessary changes in patients' management and to rule out undue biopsies as well as to differentiate them from malignancies, recurrence and/or metastases.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Incidentally, the rate of apparently positive lymphnodes was signi cant in this setting. Although our ndings may appear not astonishing, they deserve caution, particularly for cancer patients as recently reported by some other authors [23][24][25]. The correct interpretation of this secondary effect of vaccine is of primary importance to avoid unnecessary changes in patients' management and to rule out undue biopsies as well as to differentiate them from malignancies, recurrence and/or metastases.…”
Section: Discussionsupporting
confidence: 58%
“…Recently, some authors [23][24][25] have reported similar results but, in smaller cohorts, sometimes in form of case report, using one tracer and after adenovirus-based vaccine which is known to elicit in ammatory response [29]. Our study was conducted collecting data from 333 consecutive patients, irrespective of the tracer used, who underwent mRNA SARS-CoV-2 vaccination and reporting on ndings both in pre-COVID-19 period and thereafter in a subset of patients.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Overall, these articles are mainly case reports or small case series recently published by research groups from different countries worldwide reporting PET findings in COVID-19 vaccine recipients who underwent PET/CT or PET/MRI with different radiotracers for several indications [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] (Table 1). Most of the described patients underwent vaccination against COVID-19 from 1 day to 3 weeks before 18 F-FDG PET/CT.…”
mentioning
confidence: 99%
“…Less frequently, diffuse splenic 18 F-FDG-uptake was also described. All these described sites of increased radiopharmaceutical uptake were interpreted as reactive due to immune response after recent vaccination against COVID-19 [2-10, [12][13][14][15][17][18][19][20][21].…”
mentioning
confidence: 99%